Do vigorous-intensity and moderate-intensity physical activities reduce mortality to the same extent? A systematic review and meta-analysis. Issue 1 (2nd October 2020) - Rey Lopez, Juan Pablo; Sabag, Angelo; Martinez Juan, Maria; Rezende, Leandro F M; Pastor-Valero, Maria
Abstract : Objective: To examine whether vigorous-intensity physical activity confers additional reductions on all-cause and cause-specific mortality compared with moderate-intensity physical activity. Design: A systematic review (registered in PROSPERO CRD42019138995) and meta-analysis. Data sources: Three electronic databases up to April 14 2020. Eligibility criteria: Inclusion criteria were prospective studies that contained information about (1) moderate-intensity (3–5.9 metabolic equivalent tasks (METs)) and vigorous-intensity (≥6 METs) physical activities and (2) all-cause and/or cause-specific mortality. Exclusion criteria were prospective studies that (1) exclusively recruited diseased patients (eg, hypertensive patients and diabetics) or (2) did not account for total physical activity in their multivariable models (3) or did not adjust or exclude individuals with comorbidities at baseline or (4) used physically inactive participants as reference group. Results: Five studies (seven cohorts using sex-specific results) were pooled into a meta-analysis. For all-cause mortality and controlling by total physical activity, vigorous-intensity physical activity (vs moderate) was not associated with a larger reduction in mortality (HR 0.95, 95% CI 0.83 to 1.09). After the exclusion of one study judged with critical risk of bias (Risk Of Bias in Non randomized Studies, ROBINS tool) from meta-analysis, results remained similar (HR 0.98, 95% CI 0.85 to 1.12). Due to the limited number of studies, meta-analyses for cancer and cardiovascular mortality were not performed. Conclusions: Prospective studies suggest that, for the same total physical activity, both vigorous-intensity and moderate-intensity physical activities reduce all-cause mortality to the same extent. However, absence of evidence must not be interpreted as evidence of absence due to the existing methodological flaws in the literature.